SiZrOC ceramic fiber cotton and preparation method thereof
The preparation of SiZrOC ceramic fiber wool through dispersion, ultraviolet cross-linking, and heat-treatment addresses structural weaknesses in ceramic aerogels and SiOC fibers, resulting in a flexible, thermally insulating material with high compressibility and reusability.
Patent Information
- Application Number
- CN202411291507.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-01-03
AI Technical Summary
Ceramic aerogels and SiOC ceramic fibers face issues with structural collapse under thermal shock and limited flexibility, leading to damage and poor thermal insulation performance when used in high-temperature environments.
A method is developed to prepare SiZrOC ceramic fiber wool by dispersing SiZrOC ceramic fibers in a mixed solution with an organic solvent and polysiloxane, followed by ultraviolet irradiation and cross-linking, then heat-treating to form a composite integrated fiber with amorphous and crystalline structures, enhancing flexibility and thermal insulation.
The resulting SiZrOC ceramic fiber cotton exhibits low density, low thermal conductivity, and high compressibility, maintaining structural integrity under deformation, thus offering excellent thermal insulation and reusability.
Smart Images

Figure CN119243413A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thermal insulation materials, and particularly relates to SiZrOC ceramic fiber wool and a preparation method thereof. Background Art
[0002] Aerogel materials are a type of porous material with a highly three-dimensional network structure. They have the characteristics of low density, high specific surface area, and low thermal conductivity, and are widely considered to be the best thermal insulation material. Currently, the commonly used aerogel materials in high-temperature environments are silica aerogel, zirconium dioxide aerogel, etc., all of which are ceramic aerogels. Ceramic aerogels have the excellent properties of light weight, high melting point, and chemical inertness, but due to the strong directional chemical bonds between the constituent atoms and the limited sliding ability in the crystal system, when subjected to thermal shock or temperature changes, this aerogel material is difficult to dissipate external forces or internal expansion / contraction stresses by deformation, resulting in damage. At the same time, during repeated applications in high-temperature environments, due to the densification of crystalline materials, large-sized crystals, polycrystalline structures, and internal microcracks are easily formed, so aerogels are extremely prone to structural collapse, resulting in material crushing and thus being unable to be reused.
[0003] Silicon oxygen carbon ceramics (SiOC) are usually highly cross-linked precursor polymers composed of silicon, oxygen, carbon, hydrogen and other elements. They are obtained by heat treatment under certain heating conditions and atmospheres. They are a typical amorphous material. Since the amorphous structure does not have periodic phonons and electrons, silicon oxygen carbon ceramics exhibit inherent low thermal conductivity and certain thermal insulation capabilities. At the same time, silicon oxygen carbon ceramics have excellent high-temperature stability, and the maximum operating temperature can reach 1200°C, so they have important application value in the field of thermal insulation materials. Silicon oxygen carbon aerogel material has excellent properties of light weight and low thermal conductivity, but it is a typical brittle material with no deformation ability. At high temperatures, it cannot adapt to the thermal deformation of the aircraft fuselage structure. It is prone to cracking, falling off and other problems, and is difficult to reuse.
[0004] The high aspect ratio of fiber materials enables them to bend and deform over a wide range under external forces. Among them, silicon-oxygen-carbon ceramic fibers have the advantages of being lightweight and having good thermal stability, so they can be used as thermal insulation materials.
[0005] However, due to the relatively low aspect ratio of SiOC ceramic fibers, their flexibility is poor and it is difficult to combine them into a bulk insulation structure. Therefore, SiOC ceramic fibers are usually used as single films or in conjunction with other bulk components for radiation insulation. The density and thermal conductivity of the formed insulation are increased compared to SiOC ceramic fibers. Therefore, compared with SiOC ceramic fibers, the insulation formed by SiOC ceramic fibers has the problems of large mass and poor insulation performance. Summary of the invention
[0006] Therefore, the present invention provides a SiZrOC ceramic fiber wool and a preparation method thereof, the main purpose of which is to provide a ceramic fiber thermal insulation material with light weight and excellent thermal insulation performance.
[0007] In order to solve the above problems, on the one hand, the present invention provides a method for preparing SiZrOC ceramic fiber wool, comprising the following steps:
[0008] Step 1) preparing SiZrOC ceramic fiber;
[0009] Step 2) dispersing the SiZrOC ceramic fiber in a mixed solution containing an organic solvent and polysiloxane to obtain a SiZrOC fiber dispersion solution, and then coagulating the SiZrOC fiber dispersion solution to obtain a SiZrOC coagulated sample;
[0010] Step 3) subjecting the SiZrOC solidified sample to ultraviolet irradiation, and while the organic solvent remains solidified, crosslinking and curing the polysiloxane in the SiZrOC solidified sample to obtain a crosslinked solidified sample; then subjecting the crosslinked solidified sample to an organic solvent removal treatment to obtain a SiZrOC fiber cotton precursor;
[0011] Step 4) heat-treating the SiZrOC fiber cotton precursor to obtain SiZrOC ceramic fiber cotton.
[0012] Furthermore, in step 1), the step of preparing SiZrOC ceramic fiber comprises:
[0013] An SiZrOC fiber membrane precursor is prepared by using an electrospinning technique, and the SiZrOC fiber membrane precursor is heat-treated to obtain SiZrOC ceramic fibers;
[0014] Preferably, the SiZrOC ceramic fiber is a SiZrOC ceramic fiber membrane;
[0015] Preferably, the step of preparing the SiZrOC fiber membrane precursor by electrospinning technology comprises:
[0016] Preparing an electrospinning solution: preparing an electrospinning solution by mixing a zirconium source solution, polysiloxane, a photoinitiator, an electrospinning aid, and a volatile solvent; mixing the zirconium source solution, polysiloxane, and the photoinitiator to obtain a photosensitive solution; and then dissolving the photosensitive solution and the electrospinning aid in a volatile solvent to obtain an electrospinning solution;
[0017] Electrospinning treatment: Under the irradiation of ultraviolet light, the electrospinning solution is subjected to electrospinning to obtain a SiZrOC fiber membrane precursor.
[0018] Further, in the step of preparing the electrospinning solution:
[0019] The step of preparing the zirconium source solution comprises: mixing zirconium n-propoxide and acrylic acid to obtain a zirconium source solution; wherein the molar ratio of zirconium n-propoxide to acrylic acid is 1:1-2; and / or
[0020] In the photosensitive solution, the molar ratio of silicon element in the polysiloxane to zirconium element in the zirconium source solution is 1:0.5-2; and / or
[0021] Measured in percentage by mass, the electrospinning solution comprises: 15-40% of a photosensitive solution, 5-15% of an electrospinning auxiliary agent, 50-75% of a volatile solvent, and 0.1-1% of a photoinitiator.
[0022] Further, in the step of preparing the electrospinning solution: the polysiloxane is an acrylate-based polysiloxane;
[0023] Preferably, the polysiloxane is a methyl terminated acrylate polysiloxane; and / or
[0024] The photoinitiator is one or more of 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexylphenyl ketone, 2-methyl-2-(4-morpholinyl)-1-[4-(methylthio)phenyl]-1-propanone, and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide; and / or
[0025] The electrospinning aid is polyvinyl pyrrolidone; and / or
[0026] The volatile solvent is one or more of ethanol, isopropanol and N,N-dimethylformamide.
[0027] Furthermore, in the electrospinning step: the irradiation intensity of the ultraviolet lamp is 40-100 mW / cm 2 ; and / or
[0028] The wavelength of the ultraviolet lamp is 365-405nm; and / or
[0029] The ultraviolet lamp is 20-35 cm away from the electrospinning solution; and / or
[0030] The spinning voltage of electrospinning is 10-25 kV; and / or
[0031] The spinning distance of the electrospinning is 10-30 cm; and / or
[0032] The propulsion speed of the spinning head during electrospinning is 0.5-2mL / h.
[0033] Furthermore, the heat treatment step includes:
[0034] Under a protective atmosphere, the SiZrOC fiber membrane precursor is heated to 800-1200° C., kept at this temperature for 1-3 hours, and then cooled;
[0035] Preferably, the heating rate of the heat treatment is 0.5-5°C / min;
[0036] Preferably, the cooling rate of the heat treatment is 0.5-5°C / min.
[0037] Further, in the step 2):
[0038] The SiZrOC ceramic fiber is dispersed in a mixed solution containing an organic solvent and polysiloxane by shear dispersion; wherein the rotation speed of the shear dispersion is 10000-23000 rpm; the shear dispersion time is 5-30 min; and the polysiloxane is acrylate-based polysiloxane;
[0039] Preferably, the polysiloxane is a methyl terminated acrylate polysiloxane; and / or
[0040] The organic solvent is one or more of n-octanol, cyclohexane, butanol and benzene; and / or
[0041] In the mixed solution of the organic solvent and polysiloxane, the mass ratio of polysiloxane to the organic solvent is 1:100-400; and / or
[0042] The mass of the SiZrOC ceramic fiber is 0.25%-1% of the mass of the organic solvent; and / or
[0043] The solidification treatment of the SiZrOC fiber dispersion solution includes: placing the SiZrOC fiber dispersion solution in an environment below the solidification point of an organic solvent to freeze and solidify the SiZrOC fiber dispersion solution.
[0044] Further, in the step 3):
[0045] The irradiation intensity of the ultraviolet radiation is 40-100 mW / cm 2 ; The wavelength of ultraviolet radiation is 365-405nm; The time of ultraviolet radiation is 5-20min; and / or
[0046] The organic solvent removal treatment is carried out by one of freeze drying, normal pressure and normal temperature drying, normal pressure and heating drying, and vacuum and normal temperature drying.
[0047] Further, in step 4), the heat treatment step includes:
[0048] In a protective atmosphere, the SiZrOC fiber cotton precursor is heated to 800-1200° C., kept at this temperature for 1-3 hours, and then cooled;
[0049] Preferably, the heating rate of the heat treatment is 0.5-5°C / min;
[0050] Preferably, the cooling rate of the heat treatment is 0.5-5°C / min.
[0051] On the other hand, the present invention provides a SiZrOC ceramic fiber cotton, wherein the density of the SiZrOC ceramic fiber cotton is 5-25 mg / cm 3 ; The thermal conductivity of SiZrOC ceramic fiber cotton is 0.02-0.08W / (m·K); After 100 times of 40% deformation, the compression rebound rate of the SiZrOC ceramic fiber cotton is not less than 80%; The diameter of the fiber in the SiZrOC ceramic fiber cotton is 0.5-1μm; The fiber in the SiZrOC ceramic fiber cotton is a composite integrated fiber of amorphous and ZrO2 crystals, and the ZrO2 crystals are dispersed in the amorphous;
[0052] Preferably, the SiZrOC ceramic fiber wool is obtained by any of the preparation methods described above. The SiZrOC ceramic fiber wool and the preparation method thereof provided by the present invention have the following beneficial effects:
[0053] 1. The present invention disperses SiZrOC ceramic fibers in a mixed solution containing an organic solvent and polysiloxane to obtain a SiZrOC fiber dispersion solution, then solidifies the SiZrOC fiber dispersion solution to obtain a SiZrOC solidified sample; then ultraviolet irradiates the SiZrOC solidified sample, and while the organic solvent remains solidified, the SiZrOC ceramic fibers and the polysiloxane in the SiZrOC solidified sample are cross-linked and solidified to obtain a cross-linked solidified sample; then the cross-linked solidified sample is subjected to an organic solvent removal treatment to obtain a SiZrOC fiber cotton precursor; finally, the SiZrOC fiber cotton precursor is subjected to a heat treatment to obtain a SiZrOC ceramic fiber cotton; based on the above method, by treating SiZrOC The SiZrOC fiber dispersion solution is coagulated to obtain a SiZrOC coagulated sample, and then the SiZrOC coagulated sample is irradiated with ultraviolet light, and the polysiloxane in the SiZrOC coagulated sample is cross-linked and cured while the organic solvent remains in a coagulated state; wherein, the coagulation treatment combines the fibers into randomly arranged fiber blocks with a large number of holes between the fibers, so it has the advantage of being lightweight, and then after cross-linking and curing by ultraviolet radiation, the fiber skeleton, a small amount of solid skeleton (formed by cross-linking and curing of polysiloxane) and the solid organic solvent support each other, and after the organic solvent removal treatment, the structure of the fiber cotton is maintained, so that the SiZrOC ceramic fiber cotton has a low density and low thermal conductivity similar to that of aerogel materials, and therefore also has excellent thermal insulation properties.
[0054] 2. Furthermore, the SiZrOC fiber cotton precursor is heat-treated so that after SiZrOC is ceramicized, an amorphous matrix structure is formed with diffusely distributed zirconium dioxide crystals, forming a unique SiZrOC amorphous and crystalline (ZrO2) composite integrated fiber; on the one hand, the diffuse distribution of zirconium dioxide crystals brings more grain boundaries, hindering the transfer of heat, and thus having better thermal insulation performance; on the other hand, the zirconium dioxide crystals themselves have better flexibility, and the electrospinning process after zirconium element doping also makes the diameter of the fibers in the SiZrOC ceramic fiber membrane thinner, making the fibers themselves more flexible, making the prepared SiZrOC ceramic fiber cotton compressible, able to achieve multiple compression rebounds under the action of external forces, effectively adapting to the deformation, avoiding cracking, falling off and other problems, and therefore having reusability.
[0055] 3. Furthermore, the present invention combines ultraviolet light curing with electrospinning technology to prepare SiZrOC ceramic fiber membranes, and realizes cross-linking and curing of polysiloxane and zirconium source solution during the spinning process, without the need for long-term heat treatment, thereby improving the preparation efficiency of SiZrOC fiber membranes; at the same time, compared with other methods for preparing fibers, the method of combining ultraviolet light curing with electrospinning has more controllable process parameters and can prepare finer fibers, thereby making the fibers in SiZrOC ceramic fiber cotton finer.
[0056] 4. On the other hand, the present invention obtains a density of 5-25 mg / cm by the above method 3 , thermal conductivity of 0.02-0.08W / (m·K), and a compression rebound rate of not less than 80% after 100 times of 40% deformation; the fibers in the SiZrOC ceramic fiber cotton are fibers with amorphous and crystalline properties; the SiZrOC ceramic fiber cotton prepared by the present invention is light in weight, has excellent thermal insulation performance, and is reusable. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. The drawings described below are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.
[0058] Figure 1 A preparation flow chart of a lightweight heat-insulating SiZrOC ceramic fiber wool proposed in the present invention;
[0059] Figure 2 This is a microscopic morphology of the SiZrOC ceramic fiber wool prepared in Example 1;
[0060] Figure 3This is the rebound curve of the SiZrOC ceramic fiber cotton material prepared in Example 1 under 40% deformation;
[0061] Figure 4 This is a microscopic morphology of the SiZrOC ceramic fiber wool prepared in Example 2;
[0062] Figure 5 This is the rebound curve of the SiZrOC ceramic fiber cotton prepared in Example 2 under 40% deformation;
[0063] Figure 6 This is a graph showing the test results of the SiZrOC ceramic fiber wool prepared in Example 3 at 800°C back temperature;
[0064] Figure 7 This is a microscopic morphology of the SiZrOC ceramic fiber wool prepared in Example 4;
[0065] Figure 8 This is the 30% deformation compression physical object of the SiZrOC ceramic fiber wool prepared in Example 5. DETAILED DESCRIPTION
[0066] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. The drawings described below are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.
[0067] In one aspect, the present invention provides a method for preparing SiZrOC ceramic fiber wool, comprising the following steps:
[0068] Step 1) preparing SiZrOC ceramic fiber membrane;
[0069] Preparing an electrospinning solution: mixing a zirconium source solution, polysiloxane and a photoinitiator to obtain a photosensitive solution; dissolving the photosensitive solution and an electrospinning aid in a volatile solvent to obtain an electrospinning solution;
[0070] Wherein, zirconium n-propoxide and acrylic acid are mixed to obtain a zirconium source solution; wherein the molar ratio of zirconium n-propoxide to acrylic acid is 1:1; in the photosensitive solution, the molar ratio of silicon element in polysiloxane to zirconium element in the zirconium source solution is 1:0.5-2; and / or in terms of mass percentage, the electrospinning solution comprises: photosensitive solution: 20-40%, electrospinning aid: 5-15%, volatile solvent: 50-75%, photoinitiator: 0.1-1%;
[0071] The polysiloxane is acrylate-based polysiloxane, preferably methyl-terminated acrylate-based polysiloxane (i.e., polysiloxane containing methyl and acryloxypropyl groups); the photoinitiator is one or more of 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexylphenyl ketone, 2-methyl-2-(4-morpholinyl)-1-[4-(methylthio)phenyl]-1-propanone, and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide; the electrospinning auxiliary agent is polyvinyl pyrrolidone; the volatile solvent is one or more of ethanol, isopropanol, and N,N-dimethylformamide;
[0072] Electrospinning: Under the irradiation of ultraviolet light, the electrospinning solution is electrospun to obtain SiZrOC fiber membrane precursor;
[0073] Among them, the irradiation intensity of the ultraviolet lamp is 40-100mW / cm 2 ; The wavelength of the ultraviolet lamp is 365-405nm; The ultraviolet lamp is 20-35cm away from the electrospinning solution; The spinning voltage of the electrospinning is 10-25kV; The spinning distance of the electrospinning is 10-30cm; The propulsion speed of the spinning head during electrospinning is 0.5-2mL / h;
[0074] Heat treatment: heat treating the SiZrOC fiber membrane precursor to obtain a SiZrOC ceramic fiber membrane;
[0075] Specifically, under a protective atmosphere, the SiZrOC fiber membrane precursor is heated to 800-1200°C, kept at this temperature for 1-3 hours, and then cooled; wherein the heating rate of the heat treatment is 0.5-5°C / min; the cooling rate of the heat treatment is 0.5-5°C / min;
[0076] Step 2) Shearing and dispersing the SiZrOC ceramic fiber membrane in a mixed solution containing an organic solvent and polysiloxane to obtain a SiZrOC fiber dispersion solution; after the dispersion treatment, the fibers in the SiZrOC ceramic fiber membrane are broken into a structure mixed with short fibers and long fibers; then placing the SiZrOC fiber dispersion solution in an environment below the solidification point of the organic solvent to freeze and solidify the SiZrOC fiber dispersion solution to obtain a SiZrOC solidified sample, that is, the fibers are in a block shape;
[0077] The shear dispersion speed is 10000-23000rpm; the shear dispersion time is 5-30min; the polysiloxane is an acrylate polysiloxane, preferably a methyl-terminated acrylate polysiloxane; the organic solvent is one or more of n-octanol, cyclohexane, butanol, and benzene; in the mixed solution of the organic solvent and the polysiloxane, the mass ratio of the polysiloxane to the organic solvent is 1:100-400; the mass of the SiZrOC ceramic fiber membrane is 0.25%-1% of the mass of the organic solvent; for these non-reactive organic solvents in the present application, the freezing and solidification method is the simplest and fastest solidification method, and this rapid freezing and solidification method can make the fibers more evenly distributed and avoid fiber agglomeration;
[0078] Step 3) The SiZrOC solidified sample is subjected to ultraviolet irradiation, and the polysiloxane in the SiZrOC solidified sample is cross-linked and cured while the organic solvent remains solidified to obtain a cross-linked cured sample; after cross-linking and curing, the fiber skeleton, a small amount of solid skeleton (formed by cross-linking and curing of polysiloxane) and the solid organic solvent support each other; then the cross-linked cured sample is subjected to organic solvent removal treatment to obtain a lightweight, high-porosity SiZrOC fiber cotton precursor; the polysiloxane is cross-linked by ultraviolet light to form a solid, which allows the fiber to maintain its shape after the organic solvent is removed;
[0079] Among them, the irradiation intensity of ultraviolet radiation is 40-100mW / cm 2 ; The wavelength of ultraviolet irradiation is 365-405nm; The time of ultraviolet irradiation is 5-20min; The organic solvent is removed by freeze drying, normal pressure and normal temperature drying, normal pressure heating drying, vacuum and normal temperature drying;
[0080] Step 4) heat treating the SiZrOC fiber cotton precursor to obtain SiZrOC ceramic fiber cotton;
[0081] Specifically, under a protective atmosphere, the SiZrOC fiber cotton precursor is heated to 800-1200° C., kept at this temperature for 1-3 hours, and then cooled; wherein the heating rate of the heat treatment is 0.5-5° C. / min; and the cooling rate of the heat treatment is 0.5-5° C. / min.
[0082] Based on the above method, the solidification treatment combines the fibers into randomly arranged fiber blocks with a large number of holes between the fibers, so it has the advantage of being lightweight. Then, after ultraviolet radiation cross-linking and curing, the fiber skeleton, a small amount of solid skeleton (formed by cross-linking and curing of polysiloxane) and solid organic solvent support each other. After the organic solvent removal treatment, the structure of the fiber cotton is maintained, so that the SiZrOC ceramic fiber cotton has a low density and low thermal conductivity similar to that of aerogel materials, and therefore also has excellent thermal insulation properties.
[0083] The SiZrOC fiber cotton precursor is heat-treated so that after SiZrOC is ceramicized, an amorphous matrix structure and a zirconium dioxide crystal phase dispersed in the amorphous phase are formed, forming a unique SiZrOC amorphous and crystalline (ZrO2) composite integrated fiber; on the one hand, the dispersed distribution of zirconium dioxide crystals brings more grain boundaries, hindering the transfer of heat, so it has better thermal insulation performance; on the other hand, the zirconium dioxide crystals themselves have better flexibility, and the electrospinning process after zirconium element doping also makes the diameter of the fiber in the SiZrOC ceramic fiber membrane thinner, making the fiber itself more flexible, so that the prepared SiZrOC ceramic fiber cotton has compressibility, can achieve multiple compression rebound under the action of external force, effectively adapt to the deformation phase, avoid cracking, falling off and other problems, and therefore has reusability.
[0084] Among them, the conductivity after adding the zirconium source solution is better than that of the pure SiOC solution. The better conductivity makes the fiber diameter in the electrospinning process thinner. At the same time, compared with SiOC fibers, the zirconium source will have more side chain carbon elements in the photocuring doped zirconium method. These side chain carbon elements will volatilize in the form of CO and CO2 during heat treatment or remain in the fiber in the form of free carbon, making the fiber after heat treatment thinner, thereby ensuring the flexibility of the fiber in the SiZrOC ceramic fiber membrane.
[0085] On the other hand, the present invention provides a SiZrOC ceramic fiber cotton, wherein the density of the SiZrOC ceramic fiber cotton is 5-25 mg / cm 3 ; The thermal conductivity of SiZrOC ceramic fiber cotton is 0.02-0.08W / (m·K); After 100 times of 40% deformation, the compression rebound rate of SiZrOC ceramic fiber cotton is not less than 80%; The diameter of the fiber in SiZrOC ceramic fiber cotton is 0.5-1μm; The fiber in SiZrOC ceramic fiber cotton is a composite integrated fiber of amorphous and ZrO2 crystals, and the amorphous and ZrO2 crystals are dispersed;
[0086] Preferably, the SiZrOC ceramic fiber wool is obtained by any of the above preparation methods.
[0087] The present invention is further described below with reference to specific embodiments and comparative examples.
[0088] Example 1
[0089] This embodiment provides a method for preparing SiZrOC ceramic fiber wool, comprising the following steps:
[0090] Step 1) Preparation of SiZrOC ceramic fiber membrane
[0091] Prepare electrospinning solution: weigh 47g zirconium n-propoxide into a beaker, add 7.24g acrylic acid, and stir magnetically for 3h to obtain a zirconium source solution. Then weigh 10g methyl-terminated acrylate polysiloxane into a beaker, add 32.3g of the above-prepared zirconium source solution, and then add 1% 819 (phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide photoinitiator) into the beaker, and ultrasonically disperse to obtain a photosensitive solution; then dissolve 15g polyvinyl pyrrolidone powder (electrospinning aid) in a solution (volatile solvent) with a mass ratio of ethanol to N,N-dimethylformamide of 4:1 to obtain a PVP / ethanol / N,N-dimethylformamide solution with a mass fraction of 15wt%; then, take 1g of the photosensitive solution and add 2g of PVP / ethanol / N,N-dimethylformamide solution, stir magnetically for 3h to mix evenly, and obtain a stable electrospinning solution;
[0092] When preparing the zirconium source solution, the molar ratio of zirconium n-propoxide to acrylic acid is about 1:1; in the photosensitive solution, the molar ratio of silicon element in methyl-terminated acrylate polysiloxane to zirconium element in the zirconium source solution is 1:1; in terms of mass percentage, the electrospinning solution includes: photosensitive solution: 33.5%, electrospinning auxiliary agent: 8.7%, volatile solvent: 57.8%, photoinitiator: 0.3%;
[0093] Electrospinning: The electrospinning solution was placed in a 5 mL disposable syringe and installed on the electrospinning machine platform, 15 cm away from the collecting platform, and electrospinning was performed at a voltage of 15 kV (spinning voltage) and a speed of 1 mL / h (spinning propulsion speed). At a distance of 30 cm from the receiving platform (i.e., the distance between the UV lamp and the electrospinning solution), the UV light was irradiated at 80 mW / cm 2 The SiZrOC fiber membrane precursor was obtained by ultraviolet irradiation at an irradiation intensity of , wherein the electrospinning time was 40 min and the wavelength of the ultraviolet lamp was 405 nm;
[0094] Heat treatment: The SiZrOC fiber membrane precursor was placed in a tubular furnace, heated to 1000°C at a rate of 1°C / min, kept at 1000°C for 1 h, and cooled to room temperature at a rate of 5°C / min to obtain a SiZrOC ceramic fiber membrane.
[0095] Step 2) 20 mL of cyclohexane (organic solvent) was taken into a beaker, and 0.5% of the mass of cyclohexane by weight of methyl-terminated acrylate polysiloxane and 0.5% of the mass of cyclohexane by weight of SiZrOC ceramic fiber membrane were added into the beaker, and sheared and dispersed in a dispersing homogenizer at a speed of 15000 rpm for 10 min to obtain a SiZrOC fiber dispersion solution; then the container containing the SiZrOC fiber dispersion solution was placed on a -80°C cold table until the cyclohexane was completely solidified to obtain a SiZrOC frozen sample (solidified sample);
[0096] The mass of the SiZrOC ceramic fiber membrane is 0.5% of the mass of cyclohexane (organic solvent); in the mixed solution of the organic solvent and polysiloxane, the mass ratio of the methyl-terminated acrylate polysiloxane to the organic solvent is 1:200.
[0097] Step 3) The SiZrOC frozen sample is subjected to ultraviolet irradiation cross-linking and curing to obtain a cross-linked cured sample; then the cross-linked cured sample is freeze-dried at a temperature of -50°C for 12 hours to obtain a SiZrOC fiber cotton precursor; wherein the irradiation intensity of the ultraviolet irradiation is 80mW / cm 2 ; The wavelength of ultraviolet radiation is 400nm; the time of ultraviolet radiation is 10min.
[0098] Step 4) placing the SiZrOC fiber cotton precursor into a tubular furnace, heating it to 1000°C at a rate of 1°C / min, keeping it at 1000°C for 1h, and cooling it to room temperature at a rate of 5°C / min to obtain SiZrOC ceramic fiber cotton.
[0099] The microscopic morphology of the SiZrOC ceramic fiber wool prepared in this example is as follows: Figure 2 As shown in the figure, it can be seen that the SiZrOC ceramic fiber wool of this embodiment has high porosity, uniform fiber diameter, smooth surface, and good dispersion. The average diameter of the fibers in the SiZrOC ceramic fiber membrane prepared in this embodiment is 0.56 μm. The SiZrOC ceramic fiber wool prepared in this embodiment was tested and found to have a density of 10.3 mg / cm 3 , thermal conductivity is 0.024W / (m·K). Figure 3 This is the rebound curve of the SiZrOC ceramic fiber wool prepared in this embodiment under 40% deformation. It can be seen that after 100 times of 40% deformation, the compression rebound rate of the SiZrOC ceramic fiber wool in this embodiment can be measured to be 87%.
[0100] Example 2
[0101] This embodiment provides a method for preparing SiZrOC ceramic fiber wool, comprising the following steps:
[0102] Step 1) Preparation of SiZrOC ceramic fiber membrane
[0103] Preparation of electrospinning solution: weigh 47g zirconium n-propoxide into a beaker, add 7.3g acrylic acid, and stir magnetically for 3h to obtain a zirconium source solution; then weigh 10g methyl-terminated acrylate polysiloxane into a beaker, add 32.3g zirconium source solution, and then add 1% 819 (photoinitiator) into the beaker, and ultrasonically disperse to obtain a photosensitive solution; then dissolve 15g polyvinyl pyrrolidone powder (electrospinning aid) in a solution (volatile solvent) with a mass ratio of ethanol to N,N-dimethylformamide of 4:1 to obtain a PVP / ethanol / N,N-dimethylformamide solution with a mass fraction of 15wt%; then, take 1g of the photosensitive solution and add 2g of the PVP / ethanol / N,N-dimethylformamide solution, stir magnetically for 3h to mix evenly, and obtain a stable electrospinning solution;
[0104] When preparing the zirconium source solution, the molar ratio of zirconium n-propoxide to acrylic acid is about 1:1; in the photosensitive solution, the molar ratio of silicon element in methyl-terminated acrylate polysiloxane to zirconium element in the zirconium source solution is 1:1; in terms of mass percentage, the electrospinning solution includes: photosensitive solution: 33.5%, electrospinning auxiliary agent: 8.7%, volatile solvent: 57.8%, photoinitiator: 0.3%;
[0105] Electrospinning: The electrospinning solution was placed in a 5 mL disposable syringe and installed on the electrospinning machine platform, 15 cm away from the collecting platform, and electrospinning was performed at a voltage of 15 kV at a speed of 1 mL / h, and at a position 30 cm away from the receiving platform at a speed of 80 mW / cm 2 The SiZrOC fiber membrane precursor was obtained by ultraviolet irradiation at an irradiation intensity of , wherein the electrospinning time was 40 min and the wavelength of the ultraviolet lamp was 405 nm;
[0106] Heat treatment: The SiZrOC fiber membrane precursor was placed in a tubular furnace, heated to 1000°C at a rate of 1°C / min, kept at 1000°C for 1 h, and cooled to room temperature at a rate of 5°C / min to obtain a SiZrOC ceramic fiber membrane.
[0107] Step 2) 20 mL of cyclohexane (organic solvent) was taken into a beaker, and 0.25% of the mass of cyclohexane was added to the methyl-terminated acrylate polysiloxane and 0.35% of the mass of cyclohexane was added to the SiZrOC ceramic fiber membrane in the beaker, and sheared and dispersed in a dispersing homogenizer at a speed of 18000 rpm for 5 minutes to obtain a SiZrOC fiber dispersion solution; then the container containing the SiZrOC fiber dispersion solution was placed on a -80°C cold table until the cyclohexane was completely solidified to obtain a SiZrOC frozen sample (solidified sample);
[0108] The mass of the SiZrOC ceramic fiber membrane is 0.35% of the mass of the organic solvent; in the mixed solution of the organic solvent and the polysiloxane, the mass ratio of the methyl-terminated acrylate polysiloxane to the organic solvent is 1:400.
[0109] Step 3) The SiZrOC frozen sample is subjected to ultraviolet (light) irradiation cross-linking and curing to obtain a cross-linked cured sample; then the cross-linked cured sample is freeze-dried at a temperature of -50°C for 12 hours to obtain a SiZrOC fiber cotton precursor; wherein the irradiation intensity of the ultraviolet irradiation is 40 mW / cm 2 ; The wavelength of ultraviolet radiation is 365nm; the time of ultraviolet radiation is 20min.
[0110] Step 4) placing the SiZrOC fiber cotton precursor into a tubular furnace, heating it to 1000°C at a rate of 1°C / min, keeping it at 1000°C for 1h, and cooling it to room temperature at a rate of 5°C / min to obtain SiZrOC ceramic fiber cotton.
[0111] The microscopic morphology of the SiZrOC ceramic fiber wool prepared in this example is as follows: Figure 4 As shown in the figure, it can be seen that the SiZrOC ceramic fiber wool of this embodiment has larger pores and the fibers are well dispersed. The SiZrOC ceramic fiber wool prepared in this embodiment was tested and found to have a density of 5.22 mg / cm 3 , thermal conductivity is 0.024W / (m·K). Figure 5 This is the rebound curve of the SiZrOC ceramic fiber cotton prepared in this embodiment under 40% deformation. It can be seen that after 100 times of 40% deformation, the compression rebound rate of the SiZrOC ceramic fiber cotton in this embodiment can be measured to be 81%. Compared with Example 1, the strength under 40% deformation is lower, mainly because the SiZrOC ceramic fiber cotton has a low fiber content, low density, and fewer fiber overlap nodes.
[0112] Example 3
[0113] This embodiment provides a method for preparing SiZrOC ceramic fiber wool, comprising the following steps:
[0114] Step 1) Preparation of SiZrOC ceramic fiber membrane
[0115] Preparation of electrospinning solution: weigh 47g zirconium n-propoxide into a beaker, add 7.3g acrylic acid, and stir magnetically for 3h to obtain a zirconium source solution; then weigh 10g methyl-terminated acrylate polysiloxane into a beaker, add 32.3g zirconium source solution, and then add 1% 819 (photoinitiator) into the beaker, and ultrasonically disperse to obtain a photosensitive solution; then dissolve 15g polyvinyl pyrrolidone powder (electrospinning aid) in a solution (volatile solvent) with a mass ratio of ethanol to N,N-dimethylformamide of 1:1 to obtain a PVP / ethanol / N,N-dimethylformamide solution with a mass fraction of 15wt%; then, take 1g of the photosensitive solution and add 2g of the PVP / ethanol / N,N-dimethylformamide solution, stir magnetically for 3h to mix evenly, and obtain a stable electrospinning solution;
[0116] When preparing the zirconium source solution, the molar ratio of zirconium n-propoxide to acrylic acid is about 1:1; in the photosensitive solution, the molar ratio of silicon element in methyl-terminated acrylate polysiloxane to zirconium element in the zirconium source solution is 1:1; in terms of mass percentage, the electrospinning solution includes: photosensitive solution: 33.5%, electrospinning auxiliary agent: 8.7%, volatile solvent: 57.8%, photoinitiator: 0.3%;
[0117] Electrospinning: The electrospinning solution was placed in a 5 mL disposable syringe and installed on the electrospinning machine platform, 20 cm away from the collecting platform, and electrospinning was performed at a voltage of 15 kV at a speed of 0.75 mL / h, and at a position 30 cm away from the receiving platform at a speed of 90 mW / cm 2 The SiZrOC fiber membrane precursor was obtained by ultraviolet irradiation at an irradiation intensity of , wherein the electrospinning time was 60 min and the wavelength of the ultraviolet lamp was 405 nm;
[0118] Heat treatment: The SiZrOC fiber membrane precursor was placed in a tubular furnace, heated to 1000°C at a rate of 1°C / min, kept at 1000°C for 1 h, and cooled to room temperature at a rate of 5°C / min to obtain a SiZrOC ceramic fiber membrane.
[0119] Step 2) 20 mL of cyclohexane was taken in a beaker, and 0.25% of the mass of cyclohexane was added to the methyl-terminated acrylate polysiloxane and 0.5% of the mass of cyclohexane was added to the SiZrOC ceramic fiber membrane in the beaker, and sheared and dispersed in a dispersing homogenizer at a speed of 15000 rpm for 10 minutes to obtain a SiZrOC fiber dispersion solution; then the container containing the SiZrOC fiber dispersion solution was placed on a -80°C cold table until the cyclohexane was completely solidified to obtain a SiZrOC frozen sample (solidified sample);
[0120] The mass of the SiZrOC ceramic fiber membrane is 0.5% of the mass of the organic solvent; in the mixed solution of the organic solvent and the polysiloxane, the mass ratio of the methyl-terminated acrylate polysiloxane to the organic solvent is 1:400.
[0121] Step 3) The SiZrOC frozen sample is subjected to ultraviolet irradiation cross-linking and curing to obtain a cross-linked cured sample; then the cross-linked cured sample is freeze-dried at a temperature of -50°C for 12 hours to obtain a SiZrOC fiber cotton precursor; wherein the irradiation intensity of the ultraviolet irradiation is 100 mW / cm 2 ; The wavelength of ultraviolet radiation is 405nm; the time of ultraviolet radiation is 5min.
[0122] Step 4) placing the SiZrOC fiber cotton precursor into a tubular furnace, heating it to 1000°C at a rate of 1°C / min, keeping it at 1000°C for 1h, and cooling it to room temperature at a rate of 5°C / min to obtain SiZrOC ceramic fiber cotton.
[0123] The 800°C back temperature test results of the SiZrOC ceramic fiber wool prepared in this example are as follows: Figure 6 As shown, it can be seen that the SiZrOC ceramic fiber wool of this embodiment has excellent thermal insulation performance.
[0124] Example 4
[0125] This embodiment provides a method for preparing SiZrOC ceramic fiber wool, comprising the following steps:
[0126] Step 1) Preparation of SiZrOC ceramic fiber membrane
[0127] Preparation of electrospinning solution: weigh 47g zirconium n-propoxide into a beaker, add 7.3g acrylic acid, and stir magnetically for 3h to obtain a zirconium source solution; then weigh 10g methyl-terminated acrylate polysiloxane into a beaker, add 32.3g zirconium source solution, and then add 1% 819 (photoinitiator) into the beaker, and ultrasonically disperse to obtain a photosensitive solution; then dissolve 15g polyvinyl pyrrolidone powder (electrospinning aid) in a solution (volatile solvent) with a mass ratio of ethanol to N,N-dimethylformamide of 1:1 to obtain a PVP / ethanol / N,N-dimethylformamide solution with a mass fraction of 15wt%; then, take 1g of the photosensitive solution and add 2g of the PVP / ethanol / N,N-dimethylformamide solution, stir magnetically for 3h to mix evenly, and obtain a stable electrospinning solution;
[0128] When preparing the zirconium source solution, the molar ratio of zirconium n-propoxide to acrylic acid is about 1:1; in the photosensitive solution, the molar ratio of silicon element in methyl-terminated acrylate polysiloxane to zirconium element in the zirconium source solution is 1:1; in terms of mass percentage, the electrospinning solution includes: photosensitive solution: 33.5%, electrospinning auxiliary agent: 8.7%, volatile solvent: 57.8%, photoinitiator: 0.3%;
[0129] Electrospinning: The electrospinning solution was placed in a 5 mL disposable syringe and installed on the electrospinning machine platform, 20 cm away from the collecting platform, and electrospinning was performed at a voltage of 15 kV at a speed of 0.75 mL / h, and at a position 30 cm away from the receiving platform at a speed of 90 mW / cm 2 The SiZrOC fiber membrane precursor was obtained by ultraviolet irradiation at an irradiation intensity of , wherein the wavelength of the ultraviolet lamp was 405nm and the electrospinning time was 40min;
[0130] Heat treatment: The SiZrOC fiber membrane precursor was placed in a tubular furnace, heated to 1000°C at a rate of 1°C / min, kept at 1000°C for 1 h, and cooled to room temperature at a rate of 5°C / min to obtain a SiZrOC ceramic fiber membrane.
[0131] Step 2) 20 mL of cyclohexane was taken in a beaker, and 0.25% of the mass of cyclohexane was added to the methyl-terminated acrylate polysiloxane and 0.5% of the mass of cyclohexane was added to the SiZrOC ceramic fiber membrane in the beaker, and sheared and dispersed in a dispersing homogenizer at a speed of 20000 rpm for 20 minutes to obtain a SiZrOC fiber dispersion solution; then the container containing the SiZrOC fiber dispersion solution was placed on a -80°C cold table until the cyclohexane was completely solidified to obtain a SiZrOC frozen sample (solidified sample);
[0132] The mass of the SiZrOC ceramic fiber membrane is 0.5% of the mass of the organic solvent; in the mixed solution of the organic solvent and the polysiloxane, the mass ratio of the methyl-terminated acrylate polysiloxane to the organic solvent is 1:400.
[0133] Step 3) The SiZrOC frozen sample is subjected to ultraviolet irradiation cross-linking and curing to obtain a cross-linked cured sample; then the cross-linked cured sample is freeze-dried at a temperature of -50°C for 12 hours to obtain a SiZrOC fiber cotton precursor; wherein the irradiation intensity of the ultraviolet irradiation is 80mW / cm 2 ; The wavelength of ultraviolet radiation is 400nm; the time of ultraviolet radiation is 10min.
[0134] Step 4) placing the SiZrOC fiber cotton precursor into a tubular furnace, heating it to 1000°C at a rate of 1°C / min, keeping it at 1000°C for 1h, and cooling it to room temperature at a rate of 5°C / min to obtain SiZrOC ceramic fiber cotton.
[0135] The microscopic morphology of the SiZrOC ceramic fiber wool prepared in this example is as follows: Figure 7 As shown, it can be seen that the fibers in the SiZrOC ceramic fiber cotton of this embodiment are excessively sheared into short fibers due to the high rotation speed and long time during shear dispersion, which reduces the resilience of the fibers and the assembly and molding ability of the fibers.
[0136] Example 5
[0137] This embodiment provides a method for preparing SiZrOC ceramic fiber wool, comprising the following steps:
[0138] Step 1) Preparation of SiZrOC ceramic fiber membrane
[0139] Preparation of electrospinning solution: weigh 47g zirconium n-propoxide into a beaker, add 7.3g acrylic acid, and stir magnetically for 3h to obtain a zirconium source solution; then weigh 10g methyl-terminated acrylate polysiloxane into a beaker, add 32.3g zirconium source solution, and then add 1% 819 (photoinitiator) into the beaker, and ultrasonically disperse to obtain a photosensitive solution; then dissolve 15g polyvinyl pyrrolidone powder (electrospinning aid) in a solution (volatile solvent) with a mass ratio of ethanol to N,N-dimethylformamide of 4:1 to obtain a PVP / ethanol / N,N-dimethylformamide solution with a mass fraction of 15wt%; then, take 1g of the photosensitive solution and add 2g of the PVP / ethanol / N,N-dimethylformamide solution, stir magnetically for 3h to mix evenly, and obtain a stable electrospinning solution;
[0140] When preparing the zirconium source solution, the molar ratio of zirconium n-propoxide to acrylic acid is about 1:1; in the photosensitive solution, the molar ratio of silicon element in methyl-terminated acrylate polysiloxane to zirconium element in the zirconium source solution is 1:1; in terms of mass percentage, the electrospinning solution includes: photosensitive solution: 33.5%, electrospinning auxiliary agent: 8.7%, volatile solvent: 57.8%, photoinitiator: 0.3%;
[0141] Electrospinning: The electrospinning solution was placed in a 5 mL disposable syringe and installed on the electrospinning machine platform, 15 cm away from the collecting platform, and electrospinning was performed at a voltage of 15 kV at a speed of 0.75 mL / h, and at a position 30 cm away from the receiving platform at a speed of 90 mW / cm 2The ultraviolet light was irradiated at an irradiation intensity of , the wavelength of the ultraviolet light was 405 nm, and the electrospinning time was 40 min to obtain SiZrOC fiber membrane precursor;
[0142] Heat treatment: The SiZrOC fiber membrane precursor was placed in a tubular furnace, heated to 1000°C at a rate of 1°C / min, kept at 1000°C for 1 h, and cooled to room temperature at a rate of 5°C / min to obtain a SiZrOC ceramic fiber membrane.
[0143] Step 2) 20 mL of cyclohexane was taken in a beaker, and 0.5% of the mass of cyclohexane was added to the beaker. Methyl-terminated acrylate polysiloxane and 0.5% of the mass of cyclohexane were added to the SiZrOC ceramic fiber membrane. The mixture was sheared and dispersed in a dispersing homogenizer at a speed of 15000 rpm for 10 min to obtain a SiZrOC fiber dispersion solution; the container containing the SiZrOC fiber dispersion solution was then placed in a -20°C refrigerator until the cyclohexane was completely solidified to obtain a SiZrOC frozen sample (solidified sample);
[0144] The mass of the SiZrOC ceramic fiber membrane is 0.5% of the mass of the organic solvent; in the mixed solution of the organic solvent and the polysiloxane, the mass ratio of the methyl-terminated acrylate polysiloxane to the organic solvent is 1:200.
[0145] Step 3) The SiZrOC frozen sample is subjected to ultraviolet irradiation cross-linking and curing to obtain a cross-linked cured sample; then the cross-linked cured sample is freeze-dried at a temperature of -50°C for 12 hours to obtain a SiZrOC fiber cotton precursor; wherein the irradiation intensity of the ultraviolet irradiation is 80mW / cm 2 ; The wavelength of ultraviolet radiation is 400nm; the time of ultraviolet radiation is 10min.
[0146] Step 4) placing the SiZrOC fiber cotton precursor into a tubular furnace, heating it to 1000°C at a rate of 1°C / min, keeping it at 1000°C for 1h, and cooling it to room temperature at a rate of 5°C / min to obtain SiZrOC ceramic fiber cotton.
[0147] The 30% deformation compression of SiZrOC ceramic fiber wool prepared in this example is as follows: Figure 8 As shown, the fiber cotton is compressed by 30%, and after the external force is unloaded, the fiber cotton can return to its initial state without obvious deformation.
[0148] Comparative Example 1
[0149] This comparative example provides a method for preparing SiZrOC ceramic fiber cotton, comprising the following steps:
[0150] Step 1) Preparation of SiZrOC ceramic fiber membrane
[0151] Preparation of electrospinning solution: weigh 47g zirconium n-propoxide into a beaker, add 7.24g acrylic acid, and stir magnetically for 3h to obtain a zirconium source solution; then weigh 10g methyl-terminated acrylate polysiloxane into a beaker, add 32.3g zirconium source solution, and then add 1% 819 (photoinitiator) into the beaker, and ultrasonically disperse to obtain a photosensitive solution; then dissolve 15g polyvinyl pyrrolidone powder (electrospinning aid) in a solution (volatile solvent) with a mass ratio of ethanol to N,N-dimethylformamide of 4:1 to obtain a PVP / ethanol / N,N-dimethylformamide solution with a mass fraction of 15wt%; then, take 1g of the photosensitive solution and add 2g of the PVP / ethanol / N,N-dimethylformamide solution, stir magnetically for 3h to mix evenly, and obtain a stable electrospinning solution;
[0152] When preparing the zirconium source solution, the molar ratio of zirconium n-propoxide to acrylic acid is about 1:1; in the photosensitive solution, the molar ratio of silicon element in methyl-terminated acrylate polysiloxane to zirconium element in the zirconium source solution is 1:1; in terms of mass percentage, the electrospinning solution includes: photosensitive solution: 33.5%, electrospinning auxiliary agent: 8.7%, volatile solvent: 57.8%, photoinitiator: 0.3%;
[0153] Electrospinning: The electrospinning solution was placed in a 5 mL disposable syringe and installed on the electrospinning machine platform, 15 cm away from the collecting platform, and electrospinning was performed at a voltage of 15 kV at a speed of 0.75 mL / h, and at a position 30 cm away from the receiving platform at a speed of 90 mW / cm 2 The SiZrOC fiber membrane precursor was obtained by ultraviolet irradiation at an irradiation intensity of , wherein the electrospinning time was 40 min and the wavelength of the ultraviolet lamp was 405 nm;
[0154] Heat treatment: The SiZrOC fiber membrane precursor was placed in a tubular furnace, heated to 1000°C at a rate of 1°C / min, kept at 1000°C for 1 h, and cooled to room temperature at a rate of 5°C / min to obtain a SiZrOC ceramic fiber membrane.
[0155] Step 2) 20 mL of cyclohexane was taken in a beaker, 1.5% of the mass of cyclohexane was added to the methyl-terminated acrylate polysiloxane and 0.5% of the mass of cyclohexane was added to the SiZrOC ceramic fiber membrane in the beaker, and the mixture was sheared and dispersed in a dispersing homogenizer at a speed of 15000 rpm for 10 min to obtain a SiZrOC fiber dispersion solution; then the container containing the SiZrOC fiber dispersion solution was placed on a -80°C cold table until the cyclohexane was completely solidified to obtain a SiZrOC frozen sample (solidified sample);
[0156] The mass of the SiZrOC ceramic fiber membrane is 0.5% of the mass of the organic solvent; in the mixed solution of the organic solvent and the polysiloxane, the mass ratio of the methyl-terminated acrylate polysiloxane to the organic solvent is about 1:66.7.
[0157] Step 3) The SiZrOC frozen sample is subjected to ultraviolet irradiation cross-linking and curing to obtain a cross-linked cured sample; then the cross-linked cured sample is freeze-dried at a temperature of -50°C for 12 hours to obtain a SiZrOC fiber cotton precursor; wherein the irradiation intensity of the ultraviolet irradiation is 80mW / cm 2 ; The wavelength of ultraviolet radiation is 400nm; the time of ultraviolet radiation is 10min.
[0158] Step 4) placing the SiZrOC fiber cotton precursor into a tubular furnace, heating it to 1000°C at a rate of 1°C / min, keeping it at 1000°C for 1h, and cooling it to room temperature at a rate of 5°C / min to obtain SiZrOC ceramic fiber cotton.
[0159] The compression rebound effect of the SiZrOC ceramic fiber cotton prepared in this comparative example is not good. After 100 times of 40% deformation, the rebound rate is only 67%. The main reason is that there is too much methyl-terminated acrylate polysiloxane in the SiZrOC fiber dispersion solution. After cross-linking and curing, the polysiloxane forms a large number of agglomerates between the fibers, which limits the bending of the fibers under compression conditions.
[0160] Comparative Example 2
[0161] This comparative example provides a method for preparing a SiZrOC ceramic fiber membrane, comprising the following steps:
[0162] Preparation of electrospinning solution: weigh 47g zirconium n-propoxide into a beaker, add 7.24g acrylic acid, and stir magnetically for 3h to obtain a zirconium source solution; then weigh 10g methyl-terminated acrylate polysiloxane into a beaker, add 5g zirconium source solution, and then add 1% 819 (photoinitiator) into the beaker, and ultrasonically disperse to obtain a photosensitive solution; then dissolve 15g polyvinyl pyrrolidone powder (electrospinning aid) in a solution (volatile solvent) with a mass ratio of ethanol to N,N-dimethylformamide of 4:1 to obtain a PVP / ethanol / N,N-dimethylformamide solution with a mass fraction of 15wt%; then, take 1g of the photosensitive solution and add 2g of the PVP / ethanol / N,N-dimethylformamide solution, stir magnetically for 3h to mix evenly, and obtain a stable electrospinning solution;
[0163] When preparing the zirconium source solution, the molar ratio of zirconium n-propoxide to acrylic acid is about 1:1; in the photosensitive solution, the molar ratio of silicon element in methyl-terminated acrylate polysiloxane to zirconium element in the zirconium source solution is 1:0.15; in terms of mass percentage, the electrospinning solution includes: photosensitive solution: 33.5%, electrospinning auxiliary agent: 8.7%, volatile solvent: 57.8%, photoinitiator: 0.3%;
[0164] Electrospinning: The electrospinning solution was placed in a 5 mL disposable syringe and installed on the electrospinning machine platform, 15 cm away from the collecting platform, and electrospinning was performed at a voltage of 15 kV at a speed of 0.75 mL / h, and at a position 30 cm away from the receiving platform at a speed of 90 mW / cm 2 The ultraviolet light was irradiated at an irradiation intensity of , and the electrospinning time was 40 min to obtain SiZrOC fiber membrane precursor;
[0165] Heat treatment: The SiZrOC fiber membrane precursor was placed in a tubular furnace, heated to 1000°C at a rate of 1°C / min, kept at 1000°C for 1 h, and cooled to room temperature at a rate of 5°C / min to obtain a SiZrOC ceramic fiber membrane.
[0166] The average fiber diameter of the SiZrOC ceramic fiber membrane prepared in this comparative example is 1.4 μm. Since the molar ratio of the silicon element in the acrylate-based polysiloxane to the zirconium element in the zirconium source solution in the photosensitive solution of this comparative example does not satisfy 1:0.5-2, the conductivity of the electrospinning solution is relatively poor. Therefore, the diameter of the obtained precursor fiber is relatively coarse, and its flexibility is relatively poor, making it difficult to carry out the subsequent assembly into cotton steps.
[0167] It is easy for those skilled in the art to understand that, without conflict, the advantageous technical features of the above-mentioned methods can be freely combined and superimposed.
[0168] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principle of the present invention shall be included in the protection scope of the present invention. The above description is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and variations can be made without departing from the technical principles of the present invention. These improvements and variations should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing SiZrOC ceramic fiber wool, characterized in that: The following steps are involved: Step 1) preparing SiZrOC ceramic fiber; Step 2) dispersing the SiZrOC ceramic fiber in a mixed solution containing an organic solvent and polysiloxane to obtain a SiZrOC fiber dispersion solution, and then coagulating the SiZrOC fiber dispersion solution to obtain a SiZrOC coagulated sample; Step 3) subjecting the SiZrOC solidified sample to ultraviolet irradiation, and while the organic solvent remains solidified, crosslinking and curing the polysiloxane in the SiZrOC solidified sample to obtain a crosslinked solidified sample; then subjecting the crosslinked solidified sample to an organic solvent removal treatment to obtain a SiZrOC fiber cotton precursor; Step 4) heat-treating the SiZrOC fiber cotton precursor to obtain SiZrOC ceramic fiber cotton.
2. The method for preparing ceramic fiber wool according to claim 1, characterized in that: In the step 1), the step of preparing SiZrOC ceramic fiber comprises: An SiZrOC fiber membrane precursor is prepared by using an electrospinning technique, and the SiZrOC fiber membrane precursor is heat-treated to obtain SiZrOC ceramic fibers; Preferably, the SiZrOC ceramic fiber is a SiZrOC ceramic fiber membrane; Preferably, the step of preparing the SiZrOC fiber membrane precursor by electrospinning technology comprises: Preparing an electrospinning solution: preparing an electrospinning solution by mixing a zirconium source solution, polysiloxane, a photoinitiator, an electrospinning aid, and a volatile solvent; preferably, mixing the zirconium source solution, polysiloxane, and the photoinitiator to obtain a photosensitive solution; and then dissolving the photosensitive solution and the electrospinning aid in a volatile solvent to obtain an electrospinning solution; Electrospinning treatment: Under the irradiation of ultraviolet light, the electrospinning solution is subjected to electrospinning to obtain a SiZrOC fiber membrane precursor.
3. The method for preparing SiZrOC ceramic fiber wool according to claim 2, characterized in that: In the step of preparing the electrospinning solution: The step of preparing the zirconium source solution comprises: mixing zirconium n-propoxide and acrylic acid to obtain a zirconium source solution; wherein the molar ratio of zirconium n-propoxide to acrylic acid is 1:1-2; and / or In the photosensitive solution, the molar ratio of silicon element in the polysiloxane to zirconium element in the zirconium source solution is 1:0.5-2; and / or Measured in percentage by mass, the electrospinning solution comprises: 15-40% of a photosensitive solution, 5-15% of an electrospinning auxiliary agent, 50-75% of a volatile solvent, and 0.1-1% of a photoinitiator.
4. The method for preparing SiZrOC ceramic fiber wool according to claim 2 or 3, characterized in that: In the step of preparing the electrospinning solution: the polysiloxane is an acrylate-based polysiloxane; Preferably, the polysiloxane is a methyl terminated acrylate polysiloxane; and / or The photoinitiator is one or more of 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexylphenyl ketone, 2-methyl-2-(4-morpholinyl)-1-[4-(methylthio)phenyl]-1-propanone, and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide; and / or The electrospinning aid is polyvinyl pyrrolidone; and / or The volatile solvent is one or more of ethanol, isopropanol and N,N-dimethylformamide.
5. The method for preparing SiZrOC ceramic fiber wool according to claim 2, characterized in that: In the electrospinning step: the irradiation intensity of the ultraviolet lamp is 40-100 mW / cm 2 ; and / or The wavelength of the ultraviolet lamp is 365-405nm; and / or The ultraviolet lamp is 20-35 cm away from the electrospinning solution; and / or The spinning voltage of electrospinning is 10-25 kV; and / or The spinning distance of the electrospinning is 10-30 cm; and / or The propulsion speed of the spinning head during electrospinning is 0.5-2mL / h.
6. The method for preparing SiZrOC ceramic fiber wool according to claim 2, characterized in that: The heat treatment steps include: Under a protective atmosphere, the SiZrOC fiber membrane precursor is heated to 800-1200° C., kept at this temperature for 1-3 hours, and then cooled; Preferably, the heating rate of the heat treatment is 0.5-5°C / min; Preferably, the cooling rate of the heat treatment is 0.5-5°C / min.
7. The method for preparing SiZrOC ceramic fiber wool according to claim 1, characterized in that: In the step 2): The SiZrOC ceramic fiber is dispersed in a mixed solution containing an organic solvent and polysiloxane by shear dispersion; wherein the rotation speed of the shear dispersion is 10000-23000 rpm; the shear dispersion time is 5-30 min; and the polysiloxane is an acrylate-based polysiloxane; Preferably, the polysiloxane is a methyl terminated acrylate polysiloxane; and / or The organic solvent is one or more of n-octanol, cyclohexane, butanol and benzene; and / or In the mixed solution of the organic solvent and polysiloxane, the mass ratio of polysiloxane to the organic solvent is 1:100-400; and / or The mass of the SiZrOC ceramic fiber is 0.25%-1% of the mass of the organic solvent; and / or The solidification treatment of the SiZrOC fiber dispersion solution includes: placing the SiZrOC fiber dispersion solution in an environment below the solidification point of an organic solvent to freeze and solidify the SiZrOC fiber dispersion solution.
8. The method for preparing SiZrOC ceramic fiber wool according to claim 1, characterized in that: In the step 3): The irradiation intensity of the ultraviolet radiation is 40-100 mW / cm 2 ; The wavelength of ultraviolet radiation is 365-405nm; The time of ultraviolet radiation is 5-20min; and / or The organic solvent removal treatment is carried out by one of freeze drying, normal pressure and normal temperature drying, normal pressure and heating drying, and vacuum and normal temperature drying.
9. The method for preparing SiZrOC ceramic fiber wool according to claim 1, characterized in that: In step 4), the heat treatment step includes: In a protective atmosphere, the SiZrOC fiber cotton precursor is heated to 800-1200° C., kept at this temperature for 1-3 hours, and then cooled; Preferably, the heating rate of the heat treatment is 0.5-5°C / min; Preferably, the cooling rate of the heat treatment is 0.5-5°C / min.
10. A SiZrOC ceramic fiber wool, characterized in that: The density of the SiZrOC ceramic fiber cotton is 5-25 mg / cm 3 ; The thermal conductivity of SiZrOC ceramic fiber cotton is 0.02-0.08W / (m·K); After 100 times of 40% deformation, the compression rebound rate of the SiZrOC ceramic fiber cotton is not less than 80%; The diameter of the fiber in the SiZrOC ceramic fiber cotton is 0.5-1μm; The fibers in the SiZrOC ceramic fiber cotton are fibers that are composited and integrated with amorphous and ZrO2 crystals, and the ZrO2 crystals are dispersed in the amorphous; Preferably, the SiZrOC ceramic fiber wool is obtained by the preparation method according to any one of claims 1-9.
Citation Information
Patent Citations
Process for preparing ceramic fibers from polysiloxanes
CA2116813A1
Fiber-preform-reinforced aerogel insulating composite material and preparation method thereof
CN108046739A
Ceramic fiber composite aerogel thermal insulation material and preparation method thereof
CN112778017A
SiOC ceramic aerogel material and preparation method thereof
CN113773085A
Silicon-oxygen-carbon ceramic fiber membrane and preparation method thereof
CN117822147A
